Information Technologies in Education E- Learning Methodocal Complex for the Discipline “English For Specific Purposes ” (Texas Journal of Medical Science, 2023)
In this article the concept of an electronic educational-methodical complex (e-EMC) as an important tool for teaching methodologies in various disciplines, including the overall purpose and content of a subject or course, didactic processes, and forms of organization for training of the specialists for IT sphere is considered. Components and structure of the e-EMC are proposed and described in details.